2015
DOI: 10.1136/rmdopen-2015-000140
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of three single-item pain scales in patients with rheumatoid arthritis seen during routine clinical care: a comparative perspective on construct validity, reproducibility and internal responsiveness

Abstract: ObjectiveTo investigate the construct validity, reproducibility (ie, retest reliability) and internal responsiveness to treatment change of common single-item scales measuring overall pain in patients with rheumatoid arthritis (RA) and to investigate the corresponding effect of common pain-related comorbidities and medical consultation on these outcomes.Methods236 patients with RA completed a set of questionnaires including a visual analogue scale (VAS), a numerical rating scale (NRS) and a verbal rating scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 25 publications
1
30
0
4
Order By: Relevance
“…Note that this dimension has two items only ("fibromyalgia prevented me from accomplishing goals for the week" and "I was completely overwhelmed by my fibromyalgia symptoms") and three are usually recommended for scale development. However, the use of reduced, even single-item measures is frequent and has shown to be psychometrically valid in the pain literature [33]. This was the case of the "overall impact" scale in the present study, which obtained a high internal consistency score (0.81).…”
Section: Fm Impactmentioning
confidence: 47%
“…Note that this dimension has two items only ("fibromyalgia prevented me from accomplishing goals for the week" and "I was completely overwhelmed by my fibromyalgia symptoms") and three are usually recommended for scale development. However, the use of reduced, even single-item measures is frequent and has shown to be psychometrically valid in the pain literature [33]. This was the case of the "overall impact" scale in the present study, which obtained a high internal consistency score (0.81).…”
Section: Fm Impactmentioning
confidence: 47%
“…Strengths of the present study were that patients from both primary and specialist health care were included, and the relatively large sample size. Another strength was that the instruments represent different dimensions of pain (duration, distribution, and intensity), and are commonly used and validated [7, 46, 47]. There were also some important limitations of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show associations stronger than that found in the current study. For example, Sendlbeck and colleagues [41] reported correlation coefficients between .80 and .82 between these measures assessed at three different time points in a sample of patients with rheumatoid arthritis. Such strong relationships have also been found in samples of patients with chronic cancer-related pain [42] and students rating the intensity of experimentally-induced pain in the laboratory [43].…”
Section: Discussionmentioning
confidence: 99%